Development and in vivo validation of small interfering RNAs targeting NOX3 to prevent sensorineural hearing loss - Nacher-Soler, German; Marteyn, Antoine; Barenzung, Natasha; Sgroi, Stéphanie; Krause, Karl-Heinz; Senn, Pascal; Rousset, Francis (Frontiers in Neurology, 2022)
The reactive oxygen species (ROS)-generating enzyme NOX3 has recently been implicated in the pathophysiology of several acquired forms of sensorineural hearing loss, including cisplatin-, noise- and age-related hearing loss. NOX3 is highly and specifically expressed in the inner ear and therefore represents an attractive target for specific intervention aiming at otoprotection. Despite the strong rationale to inhibit NOX3, there is currently no specific pharmacological inhibitor available. Molecular therapy may represent a powerful alternative. In this study, we developed and tested a collection of small interfering (si) RNA constructs to establish a proof of concept of NOX3 inhibition through local delivery in the mouse inner ear. The inhibitory potential of 10 different siRNA constructs was first assessed in three different cells lines expressing the NOX3 complex. Efficacy of the most promising siRNA construct to knock-down NOX3 was then further assessed in vivo, comparing middle ear delivery and direct intracochlear delivery through the posterior semi-circular canal. While hearing was completely preserved through the intervention, a significant downregulation of NOX3 expression in the mouse inner ear and particularly in the spiral ganglion area at clinically relevant levels (>60%) was observed 48 h after treatment. In contrast to successful intracochlear delivery, middle ear administration of siRNA failed to significantly inhibit Nox3 mRNA expression. In conclusion, intracochlear delivery of NOX3-siRNAs induces a robust temporal NOX3 downregulation, which could be of relevance to prevent predictable acute insults such as cisplatin chemotherapy-mediated ototoxicity and other forms of acquired hearing loss, including post-prevention of noise-induced hearing loss immediately after trauma. Successful translation of our concept into an eventual clinical use in humans will depend on the development of atraumatic and efficient delivery routes into the cochlea without a risk to induce hearing loss through the intervention.